The Relationship Between Competitive Strategies And Firm Performance: A Case Of Mobile Telecommunication Companies In Kenya - Arasa, Robert; Gathinji, Loice (International Journal of Economics, Commerce and Management, 2014)
The main aim of the study was to examine the relationship between competitive strategies and organizational performance among firms in the mobile telecommunications industry in Kenya. The study identified the competitive strategies adopted by firms in the industry in Kenya, assessed the different levels of implementation of competitive strategies within the firms and examined the relationship between these strategies and firm performance. This study employed a descriptive survey design and collected data from 63 respondents out of the sample size of 72 respondents selected purposively.The study revealed that competition is high in the industry and product differentiation and low cost leadership are the most commonly used strategies. Other strategies include strategic alliance strategies and specific market focus strategies. The study concludes that the strategies adopted improves the overall firm performance. The key performance indicators influenced by these strategies include sales and market share, customer retention, profitability and product innovation. The study recommends that to achieve a low-cost advantage, a firm must have a low-cost leadership strategy, low-cost manufacturing, and a workforce committed to the low-cost strategy. Also the study recommends that when using product differentiation strategy, a company should consistently focus its efforts on providing unique product or service to enhance customer loyalty
Keywords: Competitive strategies; Performance; Firm; Telecommunications; Kenya